The comprehensive alcohol expectancy questionnaire: confirmatory factor analysis, scale refinement, and further validation - Nicolai, Jennifer; Demmel, Ralf; Moshagen, Morten (Journal of personality assessment, 2010)
The Comprehensive Alcohol Expectancy Questionnaire (CAEQ; Demmel & Hagen, 2003a, 2003b) is a self-report measure designed to assess an individual’s alcohol expectancies. In this study, we examined the CAEQ in a student sample (N= 932) and in a clinical sample of alcohol-dependent inpatients (N= 744). The Five-factor structure was confirmed by means of confirmatory factor analysis. Convergent validity of the revised CAEQ was supported by showing significant relationships to quantity and frequency of drinking. The results of this study suggest that the revised CAEQ appears to be a psychometrically sound tool for the assessment of alcohol expectancies among both students and alcohol-dependent inpatients.